Analisis Pengaruh Variasi Suhu Tempering Pada Sifat Mekanik Baja ASTM A36 Setelah Pengelasan SMAW Menggunakan Elektroda E 7016 - Gunawan, Leo Van; Satya Andika, Puger; Endramawan, Tito; Haris, Emin; Sukardi, Casiman; Satria Jati, Unggul (P3M Politeknik Negeri Cilacap, 2024)
ASTM A36 is a type of structural metal that can be applied for various purposes such as making gears, bridge structures and ship buildings. After welding, ASTM A36 steel will produce residual stress. Residual stress in the welded metal is caused not balanced temperature distribution. The method for eliminating residual stress is tempering. Tempering is used to reduce residual stresses, increase the ductility and toughness of metals. This research aims to analyze the effect of variations in tempering temperature on the mechanical properties of ASTM A36 steel after SMAW welding using E7016 electrodes. The tensile strength test on the specimen showed the highest increase due to the tempering effect of 537,880 MPa at a temperature of 200Â°C. This is proven by the reduction in material hardness of 165.07 VHN at a tempering temperature of 200Â°C when compared to the hardness of the raw material. The growth of ferrite grains in the material structure shows that the ASTM A36 material is increasingly ductile after tempering. The results of research on the effect of variations in tempering temperature on the mechanical properties of ASTM A36 can be used as an alternative way to increase ductility after the welding process